2008
DOI: 10.1016/j.clay.2007.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Clinoptilolite-rich mineral as a novel carrier for the active constituents present in Ginkgo biloba leaf extract

Abstract: The possible use of clinoptilolite-rich mineral as a novel carrier for the active constituents present in Ginkgo biloba leaf extract solutions was investigated. The flavonoid aglycone constituents were found to be selectively adsorbed on the clinoptilolite surface. The antioxidant activity determinations of the extract solutions were performed by the Trolox Equivalent Antioxidant Capacity (TEAC) assay. The antioxidant activity measurements performed for the Ginkgo leaf extract solutions showed decreasing antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…Water and exchangeable cations such as magnesium, sodium, calcium and potassium also exist in its structure. It has high potential for separation, purification, adsorption and ion exchange depending on the type of exchangeable cations and their specific positions within the framework structure [4][5][6][7][8][9][10][11][12]. Additionally, high selective cation exchange capacity makes clinoptilolite rich mineral useful in waste water treatment especially in the removal of ammonium and heavy metals such as copper, cadmium, iron, lead, nickel, silver and zinc [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Water and exchangeable cations such as magnesium, sodium, calcium and potassium also exist in its structure. It has high potential for separation, purification, adsorption and ion exchange depending on the type of exchangeable cations and their specific positions within the framework structure [4][5][6][7][8][9][10][11][12]. Additionally, high selective cation exchange capacity makes clinoptilolite rich mineral useful in waste water treatment especially in the removal of ammonium and heavy metals such as copper, cadmium, iron, lead, nickel, silver and zinc [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinoptilolite's possible side effects were controversial issues concerning therapeutic uses, the latest research reported that micronized eliminates these shortcomings and increases the efficiency of biomedical applications [12,13]. Numerous literature results report that clinoptilolite exhibits remarkable potential as a carrier platform, owing to its ability to significantly enhance both the shell life and biocompatibility of phytoconstituents in vivo, thereby facilitating controlled and prolonged release [11,13,15,[18][19][20]. Specifically, the unique physicochemical properties of clinoptilolite have been shown to effectively stabilize and protect phytoconstituents from degradation and toxicity while also improving their bioavailability and therapeutic efficacy [11,13,15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous literature results report that clinoptilolite exhibits remarkable potential as a carrier platform, owing to its ability to significantly enhance both the shell life and biocompatibility of phytoconstituents in vivo, thereby facilitating controlled and prolonged release [11,13,15,[18][19][20]. Specifically, the unique physicochemical properties of clinoptilolite have been shown to effectively stabilize and protect phytoconstituents from degradation and toxicity while also improving their bioavailability and therapeutic efficacy [11,13,15,[18][19][20]. These findings suggest that clinoptilolite represents a promising platform for the development of advanced drug delivery systems that can overcome many of the limitations associated with conventional drug delivery methods [11,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the thermal stability time of PVC‐hydrotalcite composite resins is greater than that of pure PVC resin and increases as the weight fraction of the hydrotalcite increases 12. A natural zeolite, clinoptilolite tends to neutralize the aqueous medium acting either as proton acceptor or as a proton donor due to its amphoteric character 13. Brønsted and Lewis acidic/basic sites existing in the microporous structure of the zeolitic materials are responsible for their chemical behavior in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%